« Elle avait lu Paul et Virginie » ou les moments parfaits d’Emma - Françoise Gaillard (Flaubert: Revue Critique et Génétique)
Emma dreams far less over the texts in books than over their pictures, such as the illustrated scenes in Paul et Virginie or Walter Scott’s typical images. We will study the power of these images, evil and desirable in Flaubert’s novels, and on the ontological superiority of these “perfect images” for Flaubert’s characters.